Integration of control aspects and uncertainty in the process design of polymerization reactors - Asteasuain, Mariano (2007)
In the last decades, the significant benefits of integrating control aspects in the early stages of process design have been shown. However, polymer engineering is just now incorporating this important methodology. Besides, the particularly difficult control problem of a grade transition in a polymerization reactor should be able to cope with process perturbations and uncertainty in the operating conditions and model parameters. In this work, a simultaneous process and control system design under uncertainty is performed for optimal grade transition operation. The process design includes reactor unit and initiator type selections. The control system design involves finding the best combination of controlled and manipulated variables, and the optimal controllers' tuning parameters. Discrete design decisions are incorporated by means of discrete optimization variables. The resulting optimal design minimizes off-specification product during grade transition and guarantees feasible operation in the full range of the considered uncertain parameters and process perturbations.